2018
DOI: 10.1002/hbm.23976
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal, metabolic, and therapeutic characterization of altered functional connectivity in major depressive disorder

Abstract: Although imbalanced functional integration has been increasingly reported in major depressive disorder (MDD), there still lacks a general framework to characterize common characteristic and origin shared by the integrative disturbances. Here we examined spatial selectivity, temporal uniqueness, metabolic basis, and therapeutic response of altered functional connectivity (FC) in MDD by analyzing both cross-sectional and longitudinal multimodal functional magnetic resonance imaging data from 35 patients and 34 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…SFG is part of the DMN and is related to emotional disorder and higher cognitive function ( 40 , 41 ). Past study using a voxel-wise, data-driven, graph-based approach showed significantly reduced regional connections in SFG of MDD patients ( 30 ), which is in accordance with our findings. Du et al ( 42 ) have confirmed the involvement of the SFG in the neural network dedicated to working memory.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SFG is part of the DMN and is related to emotional disorder and higher cognitive function ( 40 , 41 ). Past study using a voxel-wise, data-driven, graph-based approach showed significantly reduced regional connections in SFG of MDD patients ( 30 ), which is in accordance with our findings. Du et al ( 42 ) have confirmed the involvement of the SFG in the neural network dedicated to working memory.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, there has been greater focus on the mechanism behind the emotion disturbance in MDD patients. Studies on the emotion of MDD have centered on abnormal anatomical and functional connectivity ( 29 , 30 ). From the perspective of network topological architectures, imbalanced functional integration has been increasingly reported in MDD ( 31 , 32 ), and we are among the firsts to use graph theoretical analysis to explore the mood disturbance and cognitive function in MDD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were free of psychotropic medications for at least 4 weeks before the MRI scan and had a Hamilton depression rating (HAMD) score ≥ 14. We chose a HAMD ≥ 14 instead of 18 as in our previous studies (Shen et al, 2015 ; Sheng et al, 2018 ) to maximize the sample size of the current study. Out of the 49 patients, 26 were categorized as having AMDD in terms a HAMD anxiety/somatization factor score ≥ 7 (Fava et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Neuroimaging techniques provided a new avenue to study the pathophysiological mechanisms underlying many psychiatric disorders ( 7 12 ). With regard to PI, PET, functional, and structural MR imaging have shown abnormal glucose metabolism ( 13 ), activation ( 14 , 15 ), spontaneous activity ( 16 18 ), functional or structural connectivity ( 19 25 ), or atrophic structure ( 26 28 ) related to the cognitive system, especially the salience network (SN) ( 11 , 21 ), executive control network (ECN), and default mode network (DMN) ( 22 , 29 ).…”
Section: Introductionmentioning
confidence: 99%